The Gaia RVS benchmark stars: II. A sample of stars selected for their Gaia high radial velocity - Caffau, Elisabetta; Katz, D.; Gómez, A.; Bonifacio, P.; Lallement, R.; Sartoretti, P.; Sbordone, L.; Spite, M.; Mucciarelli, A.; Ibata, R.; Chemin, L.; Thévenin, F.; et al. (Astronomy and astrophysics, 2024)
Context. The Gaia satellite has already provided the astronomical community with three data releases, and the Radial Velocity Spectrometer (RVS) on board Gaia has provided the radial velocity for 33 million stars. Aims. When deriving the radial velocity from the RVS spectra, several stars are measured to have large values. To verify the credibility of these measurements, we selected some bright stars with the modulus of radial velocity in excess of 500 km s−1 to be observed with SOPHIE at OHP and UVES at VLT. This paper is devoted to investigating the chemical composition of the stars observed with UVES. Methods. We derived atmospheric parameters using Gaia photometry and parallaxes, and we performed a chemical analysis using the MyGIsFOS code. Results. We find that the sample consists of metal-poor stars, although none have extremely low metallicities. The abundance patterns match what has been found in other samples of metal-poor stars selected irrespective of their radial velocities. We highlight the presence of three stars with low Cu and Zn abundances that are likely descendants of pair-instability supernovae. Two stars are apparently younger than 1 Ga, and their masses exceed twice the turn-off mass of metal-poor populations. This makes it unlikely that they are blue stragglers because it would imply they formed from triple or multiple systems. We suggest instead that they are young metal-poor stars accreted from a dwarf galaxy. Finally, we find that the star RVS721 is associated with the Gjoll stream, which itself is associated with the Globular Cluster NGC 3201.